(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Femoral fracture is a significant major trauma in children and adolescents, sometimes resulting in serious complications. This study aimed to determine the epidemiology of femoral fractures and to define associated injuries and mortality incidence in a pediatric population below 16 years old. METHODS The medical records of all patients with a femoral fracture treated in our hospital from 1997–2016 were reviewed retrospectively. Age, gender, mechanism of the trauma, month and season of fracture occurrence, fracture type, associated injuries, and mortality data were collected. Patients were divided into four age groups and compared. RESULTS The study included 348 children with 353 femoral fractures. The mean annual prevalence of femoral fracture during the study period was 22.7 per 100,000 children. Except for children less than 1 year old, most fractures occurred in male patients (69%), with a male-to-female ratio of 2.2:1. Road accidents were the most common mechanism at all ages. Femoral fractures were mainly due to low-energy trauma in neonates and infants, to road accidents and low-energy trauma in preschool children, to sports accidents in school-age children, and to road traffic accidents in teenagers. February was the month with the most occurrences of femoral fractures. Winter was the peak season for femoral fractures in children aged <1 year and 6–11 years (37.8% and 46.4% of fractures respectively), whereas autumn was the most common season (29.5%) for preschool children and spring (31.1%) the most common in the teenagers group. Diaphyseal fractures were the most commonly reported lesions in all four age groups, representing 72.3% of all fractures. Only 18 fractures were open (5.1%). Eighty-eight patients (25.3%) presented with associated injuries at admission, 12 presented with Waddell’s triad of injuries, and the mortality rate was calculated to be 1.1% (four cases). CONCLUSION The circumstances of injury and the seasonality of femoral fractures differed significantly depending on the children’s ages. Moreover, the morbidity of femoral fractures in children was closely correlated with associated injuries. (Level of evidence: Level III)